Seismic fragility analysis Application to simple linear and nonlinear systems. - Kafali, Cagdas
Seismic fragility of a structural, nonstructural and/or geotechnical system is the probability that a system response exceeds a critical value under seismic ground motions of specified intensities. Fragility curves are plots of system fragilities versus a scalar measure of seismic intensity. Traditionally, peak ground acceleration (PGA) has been used as an intensity measure. Recent studies show that pseudo-spectral acceleration provides a superior measure of seismic intensity than PGA. It is shown that pseudo-spectral acceleration may not be a satisfactory measure of seismic intensity for the fragility analysis of nonlinear systems, so that fragility curves based on pseudo-spectral acceleration are not recommended for these systems. An alternative intensity measure based on two parameters, the earthquake moment magnitude m and the distance r from the seismic source to system site, is proposed for the fragility analysis of nonlinear systems. The relationship between a system probability of failure and (m, r) is called fragility surface. Findings are for single degree of freedom systems and synthetic ground motion records.
Keywords: Fragility curves; Fragility surfaces; Monte Carlo simulation; Seismic intensity measures; Specific barrier model